Hydrological Characterization of Kusa Mining Hill, Ijero-Ekiti Nigeria, Using Geo-Electrical and Electromagnetic MethodsHydrological Characterization of Kusa Mining Hill, Ijero-Ekiti Nigeria, Using Geo-Electrical and Electromagnetic Methods - Alu, Olatunji O.; Ologe, Oluwatoyin; Ogungbemi, Samuel O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
An integrated electromagnetic and geo-electric study was carried out in some parts of Kusa Mountain, Ijero Ekiti, SouthwestNigeria. Very Low Frequency Electromagnetic (VLF-EM) profiling was measured along eight traverses from whichconductive (fractured) zones were established. This enabled the location of 10 points at prominent fractured zones wherevertical electrical sounding (VES) were conducted to further reveal the geo-electric parameters. The electromagnetic andgeo-electric parameters were analysed, processed and modeled with relevant software in order to obtain the spatialdistribution of the groundwater. From the groundwater potential map, the study area was rated as low, moderate and highgroundwater potential. This study showed that central to eastern region fell within high groundwater zone. The regionaround VES 8 and 9 (northeastern flank) was rated as moderate while the remaining part is rated as having low groundwaterpotential. It is recommended that future exploration and exploitation work for groundwater resources should be concentratedaround region rated as having high groundwater potential